Sustainable financing of AYSRH programs by local governments through the TCI model - Otondi, Levis; Aloo, Nancy; Kagwe, Peter; Matekwa, Assumpta; Miriti, Kenneth; Njoki, Lilly; Sama, Denis Joel; Owino, Kenneth; Nyachae, Paul (Frontiers in Global Women's Health, 2023)
Despite having a legal policy framework for adolescent and youth sexual and reproductive health (AYSRH) services in Kenya, financing for such services has been weak. External donors have been the main financing agents, leading to concerns about the sustainability of service provision. To address this issue, Migori and Kilifi Counties partnered with The Challenge Initiative (TCI) to implement the Business Unusual model, which involved prioritizing high impact interventions (HIIs) such as integrated outreaches, youth fixed days, whole site orientation, youth champions, and youth dialogues. TCI supported the counties in adapting and implementing these interventions, while the counties committed to contributing a portion of the funding needed. The program was implemented between July 2018 and June 2021 in 60 and 68 public health facilities of Kilifi and Migori Counties, respectively. The results of the program showed a 60% increase in financial commitments on AYSRH programming from 2018 to 2021 in both counties, with an average expenditure for committed funds of 116% and 41% for Kilifi and Migori Counties, respectively. As the counties continued to allocate and spend funds on the implementation of HIIs, there was a noticeable increase in contraceptive uptake among young people aged 15 to 24 who visited health facilities for services. There was a 59% and 28% percentage increase in contraceptive uptake among young people between 2018 and 2021 in Kilifi and Migori Counties, respectively. The proportion of adolescents amongst those presenting for first ANC clinic also dropped significantly. The program also involved training master coaches who cascaded the training to over 97 coaches to build their capacity in advocacy for resource mobilization and implementation of HIIs. At least nine of TCI’s HIIs have been adopted in Kilifi and Migori County strategies and annual work plans, with financial support for their sustainability. The program's success indicates that local governments can invest in and sustain their own AYSRH programs, which will lead to improved access to contraceptive services for adolescents and youth, reducing adolescent pregnancies, maternal mortality, and infant mortality. The program's success can be attributed to system strengthening through self-financing of AYSRH programs, institutionalization of HIIs, and coaching.